Case Report: Drug-Induced Immune Haemolytic Anaemia Caused by Cefoperazone-Tazobactam/ Sulbactam Combination Therapy - Wu, Yuanjun; Wu, Yong; Ji, Yanli; Liang, Jiajie; He, Ziyi; Liu, Yanhui; Tang, Li; Guo, Ganping (Frontiers in Medicine, 2021)
There has previously been a report of a patient developing haemolytic anaemia following exposure to cefoperazone. Another case has been reported involving the detection of cefoperazone-dependent antibodies in the absence of immune haemolytic anaemia. To date, no serological evidence has been reported to suggest that cefoperazone can lead to drug-induced immune haemolytic anaemia (DIIHA). This report aims to fill these gaps in knowledge by describing a case of DIIHA caused by cefoperazone-dependent antibodies. A 59-year-old man developed fatal haemolytic anaemia while receiving cefoperazone-tazobactam or cefoperazone-sulbactam for the treatment of a lung infection that occurred after craniocerebral surgery. This eventually led to renal function impairment. Prior to the discontinuation of cefoperazone treatment, the patient showed strong positive (4+) results for both anti-IgG and anti-C3d direct antiglobulin test (DAT), while cefoperazone-dependent IgM and IgG antibodies were detected. The patient's plasma and O-type RBCs were incubated with tazobactam or sulbactam solution at 37°C for 3 h, the results of DAT for anti-IgG and anti-C3d were both positive. Forty-three days after the discontinuation of cefoperazone, the results of DAT for anti-IgG and anti-C3d were negative. Meanwhile incubation of the patient's fresh serum and his own RBCs with cefoperazone at 37°C, gave rise to mild haemolysis, and the results of DAT for both anti-IgG and anti-C3d were positive. It is suggested that cefoperazone-dependent antibodies can activate complement, and the non-immunologic protein adsorption effect of tazobactam or sulbactam can enhance IgG and complement binding to RBCs. This may promote the formation of immunocomplexes and complement activation, thereby aggravating haemolysis.